APPLICATION OF TEMPERATURE CONTROL SYSTEMS AT THE CATALYST ACTIVATION STEP IN THE METHANOL TESTPLANT - Arya Bhaskara Adiprabowo; Astri Pertiwi; Nurdiah Rahmawati; Frendy Rian Saputro; Novio Valentino; Hana Nabila Anindita; Desy Septriana (Majalah Ilmiah Pengkajian Industri, 2021)
Catalyst activation is an important step in methanol synthesis process, achieved by the reduction of CuO precursor producing Cu0 active sites.  Testplant’s temperature operation shall be maintainted at 220°C in order to maximize the CuO reduction process in the catalyst activation step. A temperature control system shall be applied in methanol testplant to maintain the temperature during reduction process, due to sensitivity of reduction process to temperature variation and possibility of disturbance such as change in gas flow rate which could affects the operating temperature. Temperature control systems are tested by using step response at the desired setpoint, which is 220°C at pre-heater and reactor and 60°C at sampling line. The tests are conducted by changing the setpoint value at temperature controller and previously stable flow gas in the system (disturbance rejection). The temperature control system proved to be able to response well during the test. In the end, methanol is produced from syngas, indicating catalyst activation success. Keywords: Catalyst Activation; Methanol Testplant; Temperature Controller